Analysis of the Influence of Brand Attitude and Brand Engagement on Positive Brand Referral Kopiko Brand - Sigit, Ilham; Ferry Tema Atmaja (Universitas Negeri Semarang, 2024)
The market for food and beverage products in Indonesia has experienced positive development, especially with the success of Kopiko candy, which reinforces its positive image among consumers. This research explores the impact of brand attitude on positive brand references among Kopiko candy consumers through brand attitude and brand engagement. Non-probability sampling employed to this study through survey resulted 311 consumers and analysed using PLS. This study findings that brand attitude indirectly influences positive brand references. Conversely, there is a positive relationship between brand attitude and brand involvement, which significantly contributes to positive brand references. Brand involvement also acts as an effective mediator in connecting brand attitude and positive brand references, with the presence of a moderating effect. This study provides a unique contribution by exploring the dual role of brand involvement as a mediating and moderating variable in the relationship between brand attitude and positive brand references, focusing on Kopiko coffee candy.